2022
DOI: 10.1016/j.bjoms.2021.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Immediate postoperative care on high dependency unit or ward following microvascular free tissue transfer: lessons learnt from a change in practice imposed during the COVID-19 pandemic

Abstract: The COVID-19 pandemic resulted in sudden changes to the established practice of using high dependency (HDU) for the first night of postoperative care following microvascular free tissue transfer. Patients were managed instead on the head and neck ward. This retrospective case-note review aimed to report outcomes in consecutive patients treated before and during the pandemic and to reflect on the implications of ward-based care rather than HDU. 235 patients had free tissue transfer between 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…This has demonstrated that patients with a newly formed elective tracheostomy can safely be discharged to a specialist ward, with suitably qualified and trained staff, immediately following major head and neck oncologic surgery. [43][44][45] Clinicians should individualize the perioperative airway protection strategy for each patient and this should be discussed and agreed upon between the operating surgeon, anesthetist, and critical care staff preoperatively (Table 3). The superiority of elective tracheostomy over delayed extubation in providing a secure airway in the postoperative period is clear and it is absolutely indicated in complex surgery and patients with a higher risk airway (Tables 3 and 4).…”
Section: The Impact Of Airway Management Strategy On Postoperative Co...mentioning
confidence: 99%
“…This has demonstrated that patients with a newly formed elective tracheostomy can safely be discharged to a specialist ward, with suitably qualified and trained staff, immediately following major head and neck oncologic surgery. [43][44][45] Clinicians should individualize the perioperative airway protection strategy for each patient and this should be discussed and agreed upon between the operating surgeon, anesthetist, and critical care staff preoperatively (Table 3). The superiority of elective tracheostomy over delayed extubation in providing a secure airway in the postoperative period is clear and it is absolutely indicated in complex surgery and patients with a higher risk airway (Tables 3 and 4).…”
Section: The Impact Of Airway Management Strategy On Postoperative Co...mentioning
confidence: 99%